PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENEMUAN TERBIMBING UNTUK MENINGKATKAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP - Yerizon, Yerizon; Sari, Widya Novita (Universitas Jenderal Soedirman, 2022)
ABSTRACT. This research is motivated by the low ability of student’s mathematical communication and the instructional package used has not provided opportunities for students to construct student’s creative ideas in understanding concepts and discovering principles. This research aims to obtain a guided discovery-based mathematics instructional package to improve mathematical communication of VIII grade junior high school students that is valid and practical. The instructional package developed is the lesson plans and student worksheets. This type of research is research and development. The development model used in this research is the Plomp model, which consists of 3 phases, namely the preliminary research phase, the development or prototyping phase, and the assessment phase. In the preliminary research phase, the analysis required for the development of guided discovery-based instructional package was carried out. In the development or prototyping phase, the design of guided discovery-based mathematics instructional package was carried out by paying attention to aspects of the feasibility of content and presentation, language, and graphics. In the development or prototyping, formative evaluation was carried out, namely self-evaluation, one-to-one evaluation, and small group evaluation. In the assessment phase, it was carried out by giving a practicality test questionnaire based on guided discovery to mathematics teachers and VIII grade students. The test subjects in this study were students of VIII.2 grade of SMPN 12 Padang in the academic year 2020/2021. The instruments used in the preliminary research phase were observation sheets, interview guides with teachers, and student questionnaires. The validity instruments were the self-evaluation sheet and the lesson plans and student worksheets validation sheet. The practical instruments were observation sheets of lesson plans, teacher response questionnaires, and student response questionnaires. The results of the analysis of the data from the lesson plans and student worksheets validation sheets show that the guided discovery-based mathematics instructional package developed is valid in terms of content and presentation, language, and graphics according to the expert judgment. Guided discovery-based mathematics instructional package are practical in terms of ease of use and time. This was obtained based on the results of observations of the implementation of the lesson plans, teacher response questionnaires, and student response questionnaires.Keywords: math learning tools, guided discovery, mathematical communication. ABSTRAK. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan komunikasi matematis peserta didik dan perangkat pembelajaran yang digunakan belum memberikan kesempatan kepada peserta didik untuk membangun ide-ide kreatif peserta didik dalam memahami konsep dan menemukan prinsip. Penelitian ini bertujuan untuk memperoleh perangkat pembelajaran matematika berbasis penemuan terbimbing untuk meningkatkan komunikasi matematis peserta didik kelas VIII SMP yang memenuhi kriteria valid dan praktis. Perangkat pembelajaran yang dikembangkan adalah Rencana Pelaksanaan Pembelajaran (RPP) dan Lembar Kerja Peserta Didik (LKPD). Jenis penelitian ini adalah penelitian pengembangan. Model pengembangan yang digunakan dalam penelitian ini adalah model plomp, yang terdiri dari 3 fase, yaitu fase investigasi awal, fase pengembangan atau pembuatan prototipe, dan fase penilaian. Fase investigasi awal dilakukan analisis yang dibutuhkan, kurikulum, konsep, dan peserta didik. Fase pengembangan prototipe dilakukan perancangan perangkat pembelajaran dengan memperhatikan aspek kelayakan isi dan penyajian, kebahasaan, dan kegrafikaan. Fase pembuatan prototipe dilakukan evaluasi formatif, yaitu evaluasi diri sendiri, evaluasi perorangan, dan evaluasi kelompok kecil. Fase penilaian dilakukan dengan memberi angket uji praktikalitas pembelajaran matematika berbasis penemuan terbimbing kepada guru matematika dan peserta didik kelas VIII. Subjek uji coba pada penelitian ini adalah peserta didik kelas VIII.2 SMPN 12 Padang Tahun Pelajaran 2020/2021. Instrumen yang digunakan pada fase investigasi awal adalah lembar observasi, pedoman wawancara dengan guru, dan angket peserta didik. Instrumen validitas adalah lembar evaluasi diri sendiri dan lembar validasi RPP dan LKPD. Instrumen kepraktisan adalah lembar observasi keterlaksanaan RPP, angket respon guru, dan angket respon peserta didik. Hasil analisis terhadap data dari lembar validasi RPP dan LKPD menunjukkan bahwa perangkat pembelajaran matematika berbasis penemuan terbimbing yang dikembangkan telah valid dari segi isi dan penyajian, kebahasaan, dan kegrafikan sesuai penilaian pakar atau ahli. Perangkat pembelajaran matematika berbasis penemuan terbimbing telah praktis dari segi kemudahan dalam penggunaan dan waktu. Hal ini diperoleh berdasarkan hasil observasi keterlaksanaan RPP, angket respon guru, dan angket respon peserta didik.Kata Kunci: perangkat pembelajaran matematika, penemuan terbimbing, komunikasi matematis.